97: Determinants of Hospital Re-Admission Following Neonatal Discharge of Extremely Preterm Infants in Canada. Issue 6 (1st June 2014) - Luu, T; Cross, S; Pillay, T; McGuire, M; Majnemer, A; de Cabo, C; Ballantyne, M; Dow, K; Synnes, A; ,
Abstract: BACKGROUND: Survivors of preterm birth are at higher risk of re-hospitalisation during infancy, especially for respiratory-related conditions. Determinants of hospital re-admission have not been studied comprehensively in Canadian preterm-born infants. OBJECTIVES: To examine whether health-related, sociodemographic and geographical factors are associated with hospital re-admission among extremely preterm infants in Canada. DESIGN/METHODS: A total of 818 preterm infants born at <29 weeks gestation between January 1st and December 31st 2010 and followed at 18 to 24 months corrected age (CA) in 26 Canadian Neonatal Follow-Up Network centers were studied. Data was collected through chart review and parental interview using standardised forms. All infants underwent a neurological examination. The association between hospital re-admission and child/family characteristics was assessed by Pearson χ 2 analyses for categorical variables and by ANOVA F-test for continuous variables. RESULTS: From neonatal discharge to 18 months CA, 271 infants (33%) were re-admitted 377 times. Re-hospitalization rates ranged from 50% for infants born at ≤23 weeks to 29% for those born at 28 weeks. Most common reasons were respiratory issues (50%), surgery (23%), infections (8%) and growth-related problems (5%). Comparisons between children re-hospitalized vs. not re-hospitalized revealed longer neonatal stay (88 vs. 73 days; P<0.01), greater proportion of infants neurologically abnormal at 18 months (20% vs. 8%; P<0.01), fewer primary caregivers subsequently employed (53% vs. 63%; P=0.02) and more on social welfare (16% vs. 8%; P=0.02) at 18 months, as well as more infants from the First Nation (8% vs. 3%, P=0.04). Marked variations across the country were observed with re-hospitalization rates between 19% and 50% for various provinces. CONCLUSIONS: Re-hospitalization of extremely preterm infants is related to neonatal, socio-demographic and regional factors. Whether geographical variations are explained by population characteristics or hospital-related practices remains to be explored.